2020
DOI: 10.3390/su12052036
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Knowledge Acquisition and Environmental Values within the Scope of a Biodiversity Learning Module

Abstract: Global biodiversity declines at unprecedented rates, mainly due to human-induced environmental change. Biodiversity conservation is, thus, highly dependent on responsible and sustainable citizenship. Educational efforts are regarded as an important means to foster awareness and pro-environmental behavior. The present study monitors two factors considered to be particularly relevant for promoting sustainable behavior: cognitive knowledge and environmental values. 205 students (Mage = 15.3) participated in a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 61 publications
3
13
0
1
Order By: Relevance
“…Especially Utilization showed a strong influence on participants' achievement. In a recent study focusing on the correlative relationship between Utilization, Preservation, and cognitive achievement within a biodiversity learning module, we have already assumed the development of a performance gap between students with high and low Utilization preferences [45]. The present study's results confirm our assumption that students with high Utilization scores will be outperformed by students holding low Utilization preferences or those scoring high on Preservation.…”
Section: Educational Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…Especially Utilization showed a strong influence on participants' achievement. In a recent study focusing on the correlative relationship between Utilization, Preservation, and cognitive achievement within a biodiversity learning module, we have already assumed the development of a performance gap between students with high and low Utilization preferences [45]. The present study's results confirm our assumption that students with high Utilization scores will be outperformed by students holding low Utilization preferences or those scoring high on Preservation.…”
Section: Educational Implicationssupporting
confidence: 85%
“…Thus, various studies in the context of environmental education have investigated how educational modules affect students' knowledge and environmental values. Knowledge acquisition has shown to be already achievable through short-term educational approaches, e.g., [45,46]. In contrast, a change in values usually requires long-term interventions and repeated occupation with the learning topic, e.g., [47].…”
Section: The Relationship Between Cognitive Achievement and Environme...mentioning
confidence: 99%
“…In addition, the study revealed that environmental education interventions were more effective when students were 18 or younger ( 5 ). Cognitive knowledge and environmental values are considered to be particularly relevant for promoting sustainable behavior ( 6 ).…”
Section: Introduction: Conservation and Science Educationmentioning
confidence: 99%
“…Among the strategies that can substantially promote the preservation of these biomes, people's education and empowerment are fundamental to transforming attitudes about nature [25][26][27]. Lasting gains depend on the acceptance of biodiversity and the reasons for its conservation [25].…”
Section: Introductionmentioning
confidence: 99%